Highly scratch-resistant tempered glass ceramic
The reinforced crystallinated glass with a (Zn, Mg)Al2O4 crystal phase and enhanced stress layers addresses the limitations of conventional glass by achieving scratch resistance comparable to sapphire glass, while being more cost-effective and easier to produce, making it suitable for high-end electronic device covers.
Patent Information
- Application Number
- JP2024502516
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-12-23
- Filing Date
- 2023-06-15
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2043-06-15
AI Technical Summary
Conventional glass materials used for protective covers in electronic devices, such as sapphire glass, face challenges in processing, cost, and limited scratch resistance, while crystallinated glass does not meet the high-end product requirements for sufficient hardness and durability.
A reinforced crystallinated glass with a compressed stress layer and tensile stress layer, containing (Zn, Mg)Al2O4 as the main crystal phase, enhanced with a high surface K2O concentration and potassium/sodium exchange depth, achieving a Young's modulus of 110-140 GPA and Vickers hardness of 750-900 kgf/mm², comparable to sapphire glass.
The enhanced crystallinated glass exhibits superior mechanical characteristics, achieving scratch resistance comparable to sapphire glass, with improved production feasibility and optical properties, suitable for high-end electronic product covers.
Smart Images

Figure 2025502907000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention claims priority based on a Chinese patent application filed with the State Intellectual Property Office of the People's Republic of China on December 23, 2022, bearing application number 202211666239.3 and entitled "Reinforced Crystallized Glass with High Scratch Resistance," the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to the field of glass material technology, and in particular to a strengthened crystallized glass having high scratch resistance. [Background technology]
[0003] Glass has excellent optical properties and is gradually being used as a protective cover for portable electronic devices, replacing plastics. For the protective cover and housing materials of portable electronic products such as smartphones, smart watches, and tablet terminals, excellent scratch resistance is required. At present, sapphire glass is a material with excellent pressure resistance and scratch resistance, but the production and processing of sapphire glass is difficult, the processing cost is high, and the tolerance for defects is low and it is easy to break. General glass has low scratch resistance, and even crystallized glass in which crystalline phases such as lithium disilicate and petalite are precipitated in glass has a limit to improving scratch resistance, making it difficult to meet the performance requirements of high-end products.
[0004] Zinc magnesium spinel crystals have a high Young's modulus and shear modulus, making them a preferred crystalline phase for improving the scratch resistance of glass.
[0005] Patent CN111615500A discloses a transparent zinc spinel-spinel glass-ceramic with spinel as the main crystal phase, which has a Young's modulus of about 98.0 GPa to about 114.0 GPa and a hardness of about 9.0 GPa to about 11.2 GPa. The scratch resistance of the glass-ceramic according to the patent is significantly improved compared to conventional crystallized glass, but the scratch resistance, Young's modulus and hardness need to be further improved. Summary of the Invention [Problem to be solved by the invention]
[0006] In view of the above-mentioned shortcomings in the prior art, an object of the present invention is to provide a strengthened crystallized glass having high scratch resistance so as to solve the problem of insufficient scratch resistance of the crystallized glass in the prior art. [Means for solving the problem]
[0007] In order to solve the above technical problems, the present invention employs the following aspects.
[0008] As a first aspect, the present invention provides a reinforced crystallized glass having high scratch resistance, the reinforced crystallized glass includes a compressive stress layer and a tensile stress layer, the main crystal phase of the reinforced crystallized glass is (Zn, Mg) Al2O4, the reinforced crystallized glass includes Na2O, the surface K2O concentration of the reinforced crystallized glass is 7.00wt% or more, optionally 7.00-15.00wt%, the depth of the reinforced crystallized glass along the thickness direction from any surface of the reinforced crystallized glass to a position near the surface and having the same potassium (K) concentration as the center of the reinforced crystallized glass is 0.07t or more, optionally 0.07t-0.10t, where t is the thickness of the reinforced crystallized glass. Optionally, when the thickness is 0.7mm, the single-rod static pressure of the reinforced crystallized glass is 450N or more, optionally 450-650N.
[0009] Optionally, the Young's modulus of the strengthened crystallized glass is 110 GPa or more, and optionally 110 to 130 GPa.
[0010] Optionally, the Vickers hardness of the strengthened crystallized glass is 750 kgf / mm 2 or more, and selectively 750~900kgf / mm 2 and selectively 800 to 900 kgf / mm 2 It is.
[0011] Optionally, in the strengthened glass-ceramics, the average crystal grain size is 15.00 nm or less, optionally 1.00 to 10.00 nm, and further optionally 4.50 to 8.00 nm.
[0012] Alternatively, in the strengthened crystallized glass, the crystal content is 20.00 to 50.00 wt%, alternatively 25.00 to 50.00 wt%, and further alternatively 25.00 to 45.00 wt%.
[0013] Optionally, the secondary crystalline phase of the strengthened glass-ceramics includes one or more selected from tetragonal ZrO2, Zn2SiO4, and Mg2SiO4.
[0014] Optionally, the strengthened glass-ceramic is transparent in the visible light range.
[0015] Optionally, a gemstone mineral hardness tester with Mohs hardness level 7 is fixed at a 45° angle using an automatic pencil hardness tester, and the surface of the reinforced crystallized glass is scratched with a load of 750 g. When the scratched crystallized glass is observed under a microscope at 400x magnification, no scratches are found on the surface of the reinforced crystallized glass.
[0016] Optionally, the tensile stress layer of the strengthened crystallized glass contains, in terms of mass percentage of oxides, 30.00%≦SiO2<35.00%, Al2O3: 30.00%-40.00%, ZnO: 10.00%-12.00%, MgO: 2.00%-4.00%, ZrO2: 5.00%-7.00%, Na2O: 2.00%-9.00%, Li2O: 0-2.00%, and B2O3: 0-8.00%, where the components of the tensile stress layer of the strengthened crystallized glass are: (1)X=((Na2O+B2O3) / ZrO2) / Al2O3, X≧2.00; (2)Y=ln[(Na2O+B2O3) / ZrO2], Y≧0; (3)Z=(SiO2+Al2O3-MgO-ZnO) / (Li2O+Na2O+B2O3), 4.00≦Z≦10.00; In the formulas (1) to (3), oxide represents the mass percentage of the oxide component; Meet the following.
[0017] Optionally, the components of the tensile stress layer of the strengthened crystallized glass further include: (4)W=(0.8×(Al2O3-SiO2)+1.5×(ZnO-MgO)) / ZrO2, 0≦W≦3.00; In formula (4), oxide represents the mass percentage of the oxide component; Meet the following.
[0018] Optionally, in the tensile stress layer of the reinforced crystallized glass, the mass percentage of SiO2 is 32.00% to 34.95%, and / or the mass percentage of Al2O3 is 32.00% to 38.00%, and / or ZnO is 10.00% to 11.48%, and / or MgO is 2.50% to 3.50%, and / or ZrO2 is 5.40% to 6.50%, and / or Na2O is 2.50% to 8.50%, and / or B2O3 is 2.50 to 8.00%.
[0019] Optionally, the tensile stress layer of the strengthened glass-ceramics further contains 0 to 3.00 wt % BaO and / or 0 to 2.00 wt % Y2O3.
[0020] Optionally, the strengthened glass-ceramics is essentially free of TiO2 and P2O5.
[0021] Alternatively, the strengthened crystallized glass is obtained by subjecting a chemical strengthening glass to a chemical strengthening treatment. The composition of the chemical strengthening glass-ceramics is essentially the same as the composition of the tensile stress layer of the strengthened crystallized glass in terms of oxide mass percentage.
[0022] Alternatively, the chemically strengthened crystallized glass is placed in a salt bath containing a potassium salt at 380°C to 550°C to carry out a chemical strengthening treatment, the chemical strengthening treatment time being 1h to 96h, and optionally 1h to 48h, thereby obtaining the strengthened crystallized glass, and the potassium salt includes one or more selected from potassium nitrate, potassium sulfate, and potassium carbonate, and optionally is potassium nitrate.
[0023] In a second aspect, the present invention further provides a chemically strengthened glass-ceramics for producing the above-mentioned strengthened glass-ceramics, the main crystal phase of the chemically strengthened glass-ceramics is (Zn,Mg)Al2O4, the molar percentage of Al2O3 in the oxide molar percentage in the chemically strengthened glass-ceramics is greater than the sum of the molar percentages of MgO and ZnO, the theoretical crystallinity of the chemically strengthened glass-ceramics is at least 30.00wt% or more, and optionally 30.00wt% to 50.00wt%, and when the chemically strengthened glass-ceramics satisfies the theoretical crystallinity, the dissociation energy U per unit volume of the residual glass phase in the glass-ceramics is 71.00kJ cm -3 or more, and selectively 71.00 kJ cm -3 ~134.00kJ cm -3 It is.
[0024] Alternatively, the chemically strengthened crystallized glass contains, in terms of mass percentage of oxides, 30.00%≦SiO2<35.00%, Al2O3: 30.00% to 40.00%, ZnO: 10.00% to 12.00%, MgO: 2.00% to 4.00%, ZrO2: 5.00% to 7.00%, Na2O: 2.00% to 9.00%, Li2O: 0 to 2.00%, and B2O3: 0 to 8.00%, and the components of the chemically strengthened crystallized glass are (1)X=((Na2O+B2O3) / ZrO2) / Al2O3, X≧2.00; (2)Y=ln[(Na2O+B2O3) / ZrO2], Y≧0; (3)Z=(SiO2+Al2O3-MgO-ZnO) / (Li2O+Na2O+B2O3), 4.00≦Z≦10.00; In the formulas (1) to (3), oxide represents the mass percentage of the oxide component; Meet the following.
[0025] Optionally, the components of the chemically strengthened crystallized glass further include: (4)W=(0.8×(Al2O3-SiO2)+1.5×(ZnO-MgO)) / ZrO2, 0≦W≦3.00; In formula (4), oxide represents the mass percentage of the oxide component; Meet the following.
[0026] Optionally, the Young's modulus of the chemically strengthened crystallized glass is 110 GPa or more, and optionally 110 to 140 GPa.
[0027] Preferably, the average crystal grain size in the chemically strengthened crystallized glass is 15.00 nm or less, preferably 1.00 to 10.00 nm, and more preferably 4.50 to 8.00 nm.
[0028] Alternatively, in the chemically strengthened crystallized glass, the crystal content is 20.00 to 50.00 wt%, alternatively 25.00 to 50.00 wt%, and further alternatively 25.00 to 45.00 wt%.
[0029] Optionally, the secondary crystal phase of the chemically strengthened crystallized glass includes one or more selected from tetragonal ZrO2, Zn2SiO4, and Mg2SiO4.
[0030] Optionally, the chemically strengthened crystallized glass further contains 0 to 3.00 wt % BaO and / or 0 to 2.00 wt % Y2O3.
[0031] Optionally, the chemically strengthened crystallized glass is essentially free of TiO2 and P2O5.
[0032] As a third aspect, the present invention further provides a glassware manufactured from the above-mentioned strengthened crystallized glass or the above-mentioned chemically strengthened crystallized glass.
[0033] As a fourth aspect, the present invention further provides an electronic device comprising the strengthened glass-ceramics or the chemically strengthened glass-ceramics. Effect of the Invention
[0034] Compared with the prior art, the present invention has the following advantageous effects:
[0035] The present invention has been intensively studied on the inherent strength of crystallized glass and the stress characteristics obtained from the glass after tempering, and has tempered a specific system of crystallized glass with high inherent strength to meet specific stress characteristics, thereby finally obtaining tempered crystallized glass with excellent scratch resistance. In the present invention, the high surface K2O concentration and high potassium-sodium exchange depth of the tempered crystallized glass give the tempered crystallized glass excellent surface stress characteristics and deep layer stress characteristics, so that when combined with the inherent high inherent strength of the crystallized glass, the mechanical properties of the tempered crystallized glass according to the present invention are greatly improved, and the tempered crystallized glass can achieve a scratch resistance effect comparable to that of sapphire glass. Based on the excellent mechanical properties and scratch resistance effects, the tempered crystallized glass of the present invention can meet the application requirements of the cover glass of high-end electronic products.
[0036] The present invention optimizes the compounding of the crystallized glass for chemical strengthening, and adjusts the relationship between the content of each oxide and each oxide in the compounding system. On the one hand, the melting difficulty of the base glass and the heat treatment temperature when manufacturing the target crystallized glass for chemical strengthening using the base glass are reduced, and the difficulty of mass-producing the crystallized glass for chemical strengthening is reduced. The glass compounding provided by the present invention can be mass-produced by ordinary continuous melting, rolling, etc. to obtain the base glass, and the moldability of the base glass can be guaranteed. And, when the heat treatment temperature of the base glass corresponding to the glass compounding according to the present invention is 800 ° C or less, the main crystal phase is a zinc magnesium spinel solid solution, and a transparent crystallized glass for chemical strengthening having good optical properties can be obtained. Compared with the prior art, the compounding system provided by the present invention can obviously reduce the heat treatment temperature, further reduce the difficulty of mass-producing the spinel crystallized glass, and improve the mass productivity of the spinel crystallized glass. On the other hand, the synergistic effect of each oxide component at a specific content provides the desired main crystal phase (Zn,Mg)Al2O4 with the desired content and improves the intrinsic strength of the residual glass phase in the chemically strengthened glass-ceramics. By combining the main crystal phase (Zn,Mg)Al2O4 with high Young's modulus and shear modulus with the residual glass phase with high intrinsic strength, the final chemically strengthened glass-ceramics has high intrinsic strength and better mechanical properties, such as scratch resistance, than conventional spinel-based glass-ceramics. [Brief description of the drawings]
[0037] [Figure 1] FIG. 1 is a TGA curve diagram of the substrate glass in Example S4. [Diagram 2] FIG. 2 shows an XRD spectrum of the chemically strengthened crystallized glass sample of Example S1. [Diagram 3] FIG. 3 is a transmittance curve diagram of the chemically strengthened crystallized glass sample of Example S1. [Figure 4]FIG. 4 is a scratch effect diagram of the scratch test conducted on the chemically strengthened crystallized glass of Example S1 under different conditions, where (a) corresponds to the test condition R1: Mohs hardness level 7 gem mineral hardness tester, load 250 g, (b) corresponds to the test condition R2: Mohs hardness level 7 gem mineral hardness tester, load 500 g, and (c) corresponds to the test condition R3: Mohs hardness level 6 gem mineral hardness tester, load 750 g. [Diagram 5] FIG. 5 is a scratch damage effect diagram obtained by conducting a scratch damage test on the chemically strengthened crystallized glass of Examples S2 and S8 under test condition R4, where test condition R4 is a gem mineral hardness tester with a Mohs hardness level of 7 and a load of 750 g, (d) corresponds to the chemically strengthened crystallized glass of Example S2, and (e) corresponds to the chemically strengthened crystallized glass of Example S8. [Figure 6] FIG. 6 is a scratch effect diagram of the reinforced crystallized glass of Example S1 subjected to a scratch test under test condition R4, in which test condition R4 is a gem mineral hardness scale with a Mohs hardness level of 7 and a load of 750 g. [Figure 7] FIG. 7 is a scratch effect diagram obtained by conducting a scratch test on the strengthened crystallized glass and sapphire glass of Examples S2 and S8 under test condition R5, where test condition R5 is a gem mineral hardness scale with a Mohs hardness level of 8 and a load of 750 g, (g) corresponds to the strengthened crystallized glass of Example S2, (h) corresponds to the strengthened crystallized glass of Example S8, and (i) corresponds to sapphire glass. [Figure 8] FIG. 8 is a scratch effect diagram of the reinforced crystallized glass of Comparative Examples D1 and D2, in which a scratch test was conducted under test condition R4, in which test condition R4 was performed using a gem mineral hardness scale with a Mohs hardness level of 7 and a load of 750 g, (j) corresponds to the reinforced crystallized glass of Comparative Example D1, and (k) corresponds to the reinforced crystallized glass of Comparative Example D2. [Figure 9]FIG. 9 is a scratch effect diagram obtained by conducting a scratch test on the chemically strengthened crystallized glass of Comparative Example D6 under test condition R3, in which test condition R3 is a gem mineral hardness tester with a Mohs hardness level of 6 and a load of 750 g, (l) corresponds to the pattern formed at the head of the scratch on the chemically strengthened crystallized glass of Comparative Example D6, and (m) corresponds to the fish scale pattern in the center of the scratch on the chemically strengthened crystallized glass of Comparative Example D6. [Figure 10] FIG. 10 is a scratch effect diagram of the reinforced crystallized glass of Comparative Example D6 subjected to a scratch test under test condition R3, in which test condition R3 is a gemstone mineral hardness tester with a Mohs hardness level of 6 and a load of 750 g. [Figure 11] FIG. 11 is an SEM image of the chemically strengthened crystallized glass of Example S3 of the present invention. [Figure 12] FIG. 12 is a relationship diagram of the concentration functions of Na2O and K2O measured by a thickness cross-sectional electron probe in the strengthened crystallized glass of Example S1. [Figure 13] FIG. 13 is a relationship diagram of the concentration functions of Na2O and K2O measured by a thickness cross-sectional electron probe in the strengthened crystallized glass of Example S2. [Figure 14] FIG. 14 is a relationship diagram of the concentration functions of Na2O and K2O measured by a thickness cross-sectional electron probe in the strengthened crystallized glass of Example D2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0038] First, the relevant special names and relevant measurement methods according to the present invention will be described below.
[0039] Base glass: Glass that has not been nucleated, crystallized, or strengthened.
[0040] Glass-ceramics: Also called glass-ceramics, these are solid composite materials that contain both a glass phase and a crystalline phase (also called a microcrystalline phase, crystallized phase, or crystalline phase) that are prepared by specifically controlling the crystallization of a base glass.
[0041] Reinforced glass-ceramics: A solid composite material obtained by chemically strengthening glass-ceramics. When performing high-temperature chemical strengthening, alkali metal ions with small ionic radii (e.g. sodium ions and lithium ions) in the glass-ceramics are replaced with alkali metal ions with large ionic radii (e.g. potassium ions and sodium ions) in the salt bath or molten salt, causing a difference in volume due to ion exchange, resulting in compressive stress on the surface of the glass-ceramics.
[0042] Residual glass phase: The non-crystalline phase in a crystallized glass system, which includes both the crystalline phase and the residual glass phase in the crystallized glass.
[0043] Dissociation energy: Generally refers to the energy required for dissociation. It is the minimum amount of energy absorbed from the outside when breaking down a molecule in its lowest energy state into completely independent atoms, and is also the energy required to break a bond.
[0044] Nucleation: The growth of small crystal nuclei in a nucleating substance in glass by heat treatment.
[0045] Crystallization: Heat treatment causes crystals to grow from crystal nuclei.
[0046] Crystalline Phase: The crystalline phase is the microscopic structure of a crystal and is determined by the conformation of the polymer chains and their arrangement in the crystal.
[0047] Theoretical Crystallinity: The theoretical maximum degree of crystallization for a crystallized glass formulation.
[0048] Average grain size: X-ray diffraction apparatus is used to measure crystallized glass sample, and the data obtained by XRD measurement is calculated to obtain the average grain size by Scherrer formula D=Kλ / (βcosθ), where λ is the wavelength of X-ray, i.e. 0.154056nm, β is the half width of diffraction peak, K=0.89, and θ is the Bragg diffraction angle. For example, the RAW file output from the XRD apparatus is curve-fitted by Jade software, and Jade outputs a fitting report, and the value of the angle 2θ corresponding to each diffraction peak in the fitting report and the value of Peak FWHM (diffraction peak half width) are converted to radians, i.e. β=(FWHM / 180×3.14), and the grain size of each diffraction peak is calculated by Scherrer formula D=Kλ / (βcosθ), and then the average is calculated to obtain the average grain size. The X-ray diffraction apparatus used in the present invention is an XRD-6100 manufactured by Shimadzu Corporation, the target material is copper, the diffraction angle range used in the measurement is 2θ=10 to 80°, the scanning speed is 0.2° / min, the operating voltage is 40 kV, and the operating current is 30 mA.
[0049] Crystal content: The percentage of the total mass of crystals in the total mass of the crystallized glass, also called the actual crystallinity. Note that both crystalline phase and crystal grain refer to the crystals precipitated in the crystallized glass, but are described differently.
[0050] Transmittance: The ratio of the radiant energy transmitted through an object to the total radiant energy incident on the object during the process in which the incident light flux is emitted from the incident surface of the irradiated surface or medium to another surface. In the examples and comparative examples of the present invention, the transmittance of crystallized glass at a wavelength of 550 nm refers to the average value of the transmittance measured at a wavelength of 550 nm for multiple glass samples of the same batch. At least five crystallized glass samples are taken from each batch and the measurement is performed.
[0051] Refractive index: the ratio of the propagation speed of light in a vacuum to the propagation speed of light in the medium. In the present invention, the refractive index of the crystallized glass piece is measured using a monocular Abbe refractometer (WYA-2WAJ, BELL Analytical Instruments Co., Ltd.) with a wavelength set to 589 nm.
[0052] b value: the yellow / blue value of a material. In the embodiments of the present invention, the b value is the b value of transmitted light. A positive b value indicates that the material is more blue. The b value is measured using a spectrophotometer CM-3600A manufactured by Konica Minolta Japan.
[0053] Vickers hardness: A standard for expressing the hardness of materials proposed by Robert L. Smith and George E. Sandland of the UK at Vickers Ltd in 1921.
[0054] Sample thickness measurement: measured by a micrometer. Although the degree of ion exchange in the thickness direction changes in a gradient from the surface to the center, the total Na-K and / or Li-Na exchange amount generally does not exceed 1% of the total mass of the sample, and the difference in ion radius is at the pm level, so it can be approximately considered that the expansion effect in the thickness direction is extremely slight and the thickness basically does not change. In other words, the change in thickness of the crystallized glass piece before and after chemical strengthening is very small and can be ignored.
[0055] Optical property measurement: referring to the standard "GB / T 7962.12-2010 Colorless Optical Glass Measurement Method Part 12: Spectral Transmittance", the haze, b value and transmittance of the crystallized glass are measured using specialized measuring equipment. In the present invention, the haze and b value are measured using a spectrophotometer CM-3600A manufactured by Konica Minolta Japan. In the present invention, the transmittance and its curve are measured using a UV-2000 ultraviolet-visible spectrophotometer manufactured by Shimadzu Corporation.
[0056] Measurement method of crystal content: Use an X-ray diffraction apparatus to measure the crystallized glass sample, obtain the XRD measurement result, and introduce the measurement result file (RAW format) of the X-ray diffraction apparatus into the X-ray diffraction data Rietveld Rietveld refinement software (e.g., Gsas, Fullprof, Maud), perform fitting and calculation, and the ratio value of the fitted crystalline phase peak area to the fitted total peak area is the crystal content. The X-ray diffraction apparatus used in the present invention is Shimadzu XRD-6100, the target material is copper, the diffraction angle range used in the measurement is 2θ=10~80°, the scanning speed is 0.2° / min, the operating voltage is 40kV, and the operating current is 30mA.
[0057] Density measurement: The density of the crystallized glass samples is measured according to the principle of "Archimedes' method", and the measuring instrument is ALFA MIRAGE electronic specific gravity meter SD-200L.
[0058] Measurement of Young's modulus: The measurement instrument is a UMS-100 ultrasonic material characterization system.
[0059] Differential scanning calorimetry (DSC) measurement: The measurement equipment is a Mettler Toledo TGA / DSC3+ thermogravimetry and simultaneous thermal analysis device. During measurement, the sample is powdered and passed through a 200 mesh sieve. The measurement conditions are room temperature to 1100°C, with a heating rate of 10°C / min. The standard material used in the measurement is α-Al2O3 powder, and the temperature of the environment in which the equipment is installed is 24°C, with an air humidity of 40%.
[0060] Single rod static pressure: Place the strengthened crystallized glass in the bottom ring of the tensile tester (LT-850A), start the measurement software, set the moving speed of the pressing rod (rod diameter 8 mm, indenter arc radius 10 mm) to 50 mm / min, and click Start Measurement. The pressing rod will apply force to the center of the crystallized glass piece to be measured according to the set moving speed until the crystallized glass cracks and breaks. The measurement software automatically reads the force (N) at which the glass breaks as the measurement result. Ten crystallized glass samples in the same condition are measured, and the average of the measurement results is taken as the single rod static pressure strength of the crystallized glass.
[0061] Scratch damage measurement: The measuring device is an automatic pencil hardness tester (ZIPANG MOTOR). Measurement method: The scratch damage test is performed by fixing the Mohs hardness tester at an angle of 45° using the automatic pencil hardness tester, contacting its tip with the surface of the glass sample, and moving the glass mounting table at a moving speed of 60 mm / min under a specified load. The wiped glass sample to be measured is placed on the glass mounting table, and the specified load is set by placing a weight of the corresponding weight on it. The gem mineral hardness tester No. 6 to 8 used in the present invention corresponds to Mohs hardness levels 6 to 8, respectively. After the scratch damage test is completed, the scratched glass sample is placed under a microscope with a magnification of 400, and the state of the scratch damage is observed, photographed, and recorded. The hardness of the measured glass sample is judged depending on the presence or absence of scratches and the state of the scratches. If there are scratches, it means that the hardness of the measured glass sample is lower than that of the hardness tester for measurement, and if there are no scratches, it means that the hardness of the measured glass sample is higher than that of the hardness tester for measurement.
[0062] Electron probe measurement: The measuring device is an electron probe EPMA-1720 manufactured by Shimadzu Corporation. A component analysis of a microscopic area is performed using characteristic X-rays generated by applying an electron beam to a sample. In the present invention, the depth of the compressive stress layer formed by potassium-sodium exchange in the strengthened crystallized glass obtained by chemical strengthening is measured by the electron probe.
[0063] Measurement of surface K2O concentration: Surface K2O concentration is equal to K2O mass divided by total mass of oxides, where the total mass of oxides includes the content of oxides that can be accurately measured by XRF, such as SiO2, Al2O3, P2O5, ZrO2, Na2O, and K2O, and does not include the content of oxides that cannot be accurately measured by XRF, such as Li2O and B2O3. The surface K2O concentration of the strengthened crystallized glass according to the present invention is obtained by measuring with an X-ray fluorescence spectrometer (XRF), and the instrument used for the measurement is Thermo Scientific ARL (registered trademark) PERFORM'X. The target material is Rh (rhodium), the tube voltage is 40 kW, the current is 60 mA, the collimator is 0.15, the crystal is selected as LiF200, the detector is selected as FPC, the measurement range is a circle of 29 mm, and the analysis software is UniQuant, for performing standardless analysis. During XRF measurement, standardless measurement is used, but the mass of elements with atomic numbers of 6 or less in the glass and their oxides is not measured. That is, in the present invention, when the K2O concentration obtained by XRF measurement is calculated, the total mass of oxides does not include the mass of elements in the glass with atomic numbers of 6 or less and their oxides.
[0064] Vickers hardness (HV) measurement: The chemically strengthened crystallized glass pieces are made into small pieces of 50 mm long x 50 mm wide x 0.7 mm thick, and the glass samples with clean surfaces and no visible scratches, dents, cracks, or other damage are selected as measurement samples, and then the Vickers hardness of the strengthened crystallized glass is measured using a Vickers hardness tester. Measurement conditions: the load is 300 gf, the load time is 10 s, and the indentation effectiveness is in accordance with GB / T 16534. Three different points on the surface of the same sample are selected for measurement, and the average value of the three measurement results is the final measurement result. The Vickers hardness tester used in the present invention is a digital low-load Vickers hardness tester (Beijing Kewei Technology Co., Ltd., VTD405).
[0065] 2. Strengthened crystallized glass with high scratch resistance and crystallized glass for chemical strengthening
[0066] As a result of examining the components of conventional crystallized glass, the present invention has found that zinc-magnesium spinel crystals have high Young's modulus and shear modulus, making them a preferred crystalline phase for improving the scratch resistance of glass. However, the scratch resistance of conventional transparent spinel crystallized glass is not sufficient to meet the application requirements of protective covers for high-end products, and needs to be further improved.
[0067] The present invention provides a reinforced crystallized glass having high scratch resistance, the reinforced crystallized glass includes a compressive stress layer and a tensile stress layer, and the main crystal phase of the reinforced crystallized glass is (Zn,Mg)Al2O4. The reinforced crystallized glass includes Na2O. The surface K2O concentration of the reinforced crystallized glass is 7.00wt% or more, and optionally 7.00-15.00wt%. In the reinforced crystallized glass, the depth from any surface of the reinforced crystallized glass to a position near the surface and having the same potassium (K) concentration as the center of the reinforced crystallized glass along the thickness direction of the glass is 0.07t or more, and optionally 0.07t-0.10t, where t is the thickness of the reinforced crystallized glass.
[0068] The present invention has been made by thoroughly studying the inherent strength of glass-ceramics and the stress characteristics obtained by the glass after tempering, and by tempering a specific system of chemically tempered glass-ceramics with high inherent strength to satisfy specific stress characteristics, finally obtaining tempered glass-ceramics with excellent scratch resistance. In the present invention, the high surface K2O concentration and high potassium-sodium exchange depth of the tempered glass-ceramics give the tempered glass-ceramics excellent surface stress characteristics and deep layer stress characteristics, and when combined with the inherent high inherent strength of the chemically tempered glass-ceramics, the mechanical properties of the tempered glass-ceramics according to the present invention are greatly improved, and the tempered glass-ceramics can achieve a scratch resistance effect comparable to that of sapphire glass.
[0069] After the chemical strengthening ion exchange process is performed, the composition on the surface of the crystallized glass may differ from that of the freshly formed crystallized glass (i.e., the crystallized glass for chemical strengthening that has not been ion-exchanged). In other words, the composition of the compressive stress layer formed by ion exchange on the surface of the strengthened crystallized glass may differ from that of the crystallized glass for chemical strengthening. This is because, during the ion exchange, one type of alkali metal ion (e.g., Li + or Na + ) is a large alkali metal ion (e.g., Na + or K + ) is substituted, for example, Na in glass + In the enrichment salt bath, + was replaced by K + and / or Li in the glass + Na in the enhanced salt bath + is exchanged for Na + However, in the embodiment, the composition of the crystallized glass at the center of the depth of the glass product or near the center of the depth still has the composition of the crystallized glass just formed. That is, the composition of the tensile stress layer that has not been ion-exchanged in the strengthened crystallized glass still has the composition of the crystallized glass for chemical strengthening. As a result, the potassium concentration at the center of the strengthened crystallized glass still has the potassium concentration of the composition of the crystallized glass for chemical strengthening.
[0070] In the chemical strengthening process, exchange of alkali metal ions occurs, but the main crystal phase of the chemically strengthened glass-ceramics of the present invention is (Zn,Mg)Al2O4, the sub-crystal phase contains one or more selected from tetragonal ZrO2, Zn2SiO4, and Mg2SiO4, does not contain alkali metals, and is not involved in ion exchange, so the composition of the crystal phase does not change basically before and after strengthening. Therefore, the main crystal phase of the strengthened glass-ceramics obtained by chemical strengthening is still (Zn,Mg)Al2O4, and the sub-crystal phase contains one or more selected from tetragonal ZrO2, Zn2SiO4, and Mg2SiO4.
[0071] In some embodiments of the present invention, the surface K2O concentration of the strengthened crystallized glass is 7.00wt% or more, and optionally 7.00-15.00wt%. In some embodiments, the surface K2O concentration is 7.00wt%-8.00wt%, 7.00wt%-9.00wt%, 7.00wt%-10.00wt%, 7.00wt%-11.00wt%, 7.00wt%-12.00wt%, 7.00wt%-13.00wt%, 7.00wt%-14.00wt%, 7.00wt%-15.00wt%, 8 ...8.00wt%, 7.00wt%-8.00wt 0.00wt%-10.00wt%, 9.00wt%-14.00wt%, 9.00wt%-13.00wt%, 7.00wt%, 8.00wt%, 9.00wt%, 10.00wt%, 11.00wt%, 12.00wt%, 13.00wt%, 14.00wt%, 15.00wt%, etc., and all ranges and subranges therebetween.
[0072] In the strengthened crystallized glass, the depth from any surface of the strengthened crystallized glass to a position near the surface and having the same potassium (K) concentration as the center of the strengthened crystallized glass along the thickness direction of the glass is 0.07t or more, and optionally 0.07t to 0.10t, where t is the thickness of the strengthened crystallized glass. In some embodiments, the depth from any surface of the strengthened crystallized glass to a position near the surface and having the same potassium (K) concentration as the center of the strengthened crystallized glass along the thickness direction of the glass can be 0.07t to 0.08t, 0.07t to 0.09t, 0.08t to 0.09t, 0.08t to 0.10t, 0.09t to 0.10t, 0.07t, 0.08t, 0.09t, 0.10t, etc., and all ranges and subranges between the above values. For example, when the thickness of the strengthened crystallized glass is 0.7 mm, the depth from any surface of the strengthened crystallized glass to a position that is close to the surface and has the same potassium (K) concentration as the center of the strengthened crystallized glass along the thickness direction of the glass is 49.00 μm or more, and optionally 49.00 μm to 70.00 μm, and further 49.00 μm to 55.00 μm, 49.00 μm to 60.00 μm. The range may be, for example, 49.00 μm, 50.00 μm, 50.00 μm, 60.00 μm, 50.00 μm, 70.00 μm, 60.00 μm, 70.00 μm, 55.00 μm, 70.00 μm, 65.00 μm, 70.00 μm, etc., and all ranges and subranges therebetween. Note that in the embodiments, any of the above ranges may be combined with any other range. In the present invention, the greater the depth from any surface of the strengthened crystallized glass to a position near that surface and having a potassium (K) concentration similar to that of the center of the strengthened crystallized glass, the deeper the penetration of K ions in the salt bath into the crystallized glass during chemical strengthening, and therefore the deeper the compressive stress layer formed in the strengthened crystallized glass by potassium-sodium exchange (referring to the exchange between potassium ions in the salt bath and Na ions in the crystallized glass).
[0073] In some embodiments of the present invention, when the thickness is 0.7 mm, the single rod static pressure strength of the strengthened crystallized glass is 450N or more, optionally 450-650N. In some embodiments, the single rod static pressure strength of the strengthened crystallized glass may be 450N-500N, 450N-600N, 450N-490N, 480N-570N, 470N-610N, 520N-650N, 540N-630N, 450N, 500N, 550N, 600N, 650N, etc., and all ranges and subranges therebetween. Note that in the embodiments, any of the above ranges can be combined with any other range.
[0074] In some embodiments of the present invention, the Young's modulus of the chemically strengthened crystallized glass is 110.00 GPa or more, and optionally 110.00 GPa to 140.00 GPa. In addition, in the present invention, after chemical strengthening, the Young's modulus of the crystallized glass increases appropriately, so the Young's modulus of the strengthened crystallized glass is 110 GPa or more, and optionally 110 to 140 GPa. In some embodiments, the Young's modulus of the strengthened crystallized glass may be 110GPa-140GPa, 110GPa-115GPa, 110GPa-120GPa, 110GPa-125GPa, 115GPa-128GPa, 121GPa-129GPa, 114GPa-127GPa, 113GPa-129GPa, 126GPa-130GPa, 110GPa, 115GPa, 118GPa, 120GPa, 123GPa, 126GPa, 130GPa, 135GPa, 140GPa, etc., and all ranges and subranges therebetween. Note that in the embodiments, any of the above ranges may be combined with any other range.
[0075] In some embodiments of the present invention, the Vickers hardness of the strengthened crystallized glass is 750 kgf / mm 2 or more, and selectively 750~900kgf / mm 2 and selectively 800 to 900 kgf / mm 2 In some embodiments, the strengthened crystallized glass has a Vickers hardness of 750 kgf / mm2 ~810kgf / mm 2 , 800kgf / mm 2 ~820kgf / mm 2 , 810kgf / mm 2 ~850kgf / mm 2 , 840kgf / mm 2 ~880kgf / mm 2 , 860kgf / mm 2 ~890kgf / mm 2 , 870kgf / mm 2 ~900kgf / mm 2 , 850kgf / mm 2 ~880kgf / mm 2 , 830kgf / mm 2 ~845kgf / mm 2 , 860kgf / mm 2 ~875kgf / mm 2 , 750kgf / mm 2 , 800kgf / mm 2 , 820kgf / mm 2 , 845kgf / mm 2 , 860kgf / mm 2 , 870kgf / mm 2 , 885kgf / mm 2 , 890kgf / mm 2 and so forth, and all ranges and subranges therebetween. It should be noted that in practice, any of the above ranges can be combined with any other range.
[0076] In some embodiments of the present invention, the average grain size of the chemically strengthened crystallized glass is 15.00 nm or less, optionally 1.00-10.00 nm, and more preferably 4.50-8.00 nm. In the present invention, the chemical strengthening process does not significantly change the grain size, so the average grain size in the strengthened crystallized glass is 15.00 nm or less. In some embodiments, the average grain size is 1.00 nm to 4.00 nm, 1.00 nm to 9.00 nm, 1.00 nm to 13.00 nm, 3.00 nm to 5.00 nm, 6.00 nm to 10.00 nm, 7.00 nm to 9.00 nm, 5.00 nm to 6.00 nm, 5.00 nm to 7.00 nm, 5.00 nm to 8.00 nm, 6.00 nm to 8.00 nm, 8.00 nm to 10.00 nm, 7.00 nm to 12. 00 nm, 1.00 nm, 2.00 nm, 3.00 nm, 4.00 nm, 5.00 nm, 6.00 nm, 7.00 nm, 8.00 nm, 9.00 nm, 10.00 nm, 11.00 nm, 12.00 nm, 13.00 nm, 14.00 nm, 15.00 nm, etc., and all ranges and subranges therebetween, optionally from 1.00 to 10.00 nm, and more optionally from 4.50 to 8.00 nm, etc. In the embodiments, any of the above ranges can be combined with any other range.
[0077] In some embodiments of the present invention, the crystal content of the chemically strengthened crystallized glass is 20.00-50.00wt%, alternatively 25.00-50.00wt%, and more alternatively 25.00-45.00wt%. The main crystal phase of the chemically strengthened crystallized glass according to the present invention is (Zn,Mg)Al2O4, and the sub-crystal phase contains one or more selected from tetragonal ZrO2, Zn2SiO4, and Mg2SiO4, and does not contain alkali metal ions, so it does not participate in ion exchange. Therefore, in the strengthened crystallized glass, the crystal content is maintained at 20.00-50.00wt%, alternatively 25.00-50.00wt%, and more alternatively 25.00-45.00wt%. In some embodiments, the strengthened glass-ceramics may have a crystalline content of 20.00wt%, 25.00wt%, 28.00wt%, 30.00wt%, 33.00wt%, 35.00wt%, 38.00wt%, 40.00wt%, 43.00wt%, 45.00wt%, 48.00wt%, 50.00wt%, etc., and all ranges and subranges therebetween, including any of the above ranges, which may be combined with any other range in the implementation.
[0078] In some embodiments of the present invention, when the thickness is 0.7 mm, the transmittance of the chemically strengthened crystallized glass for light with a wavelength of 550 nm is 85.00% or more, and optionally 89.00% or more. In addition, in the present invention, the transmittance of the crystallized glass is basically unchanged after chemical strengthening treatment. Therefore, the strengthened crystallized glass is transparent in the visible light range and still has basically the same transmittance as the chemically strengthened crystallized glass.
[0079] In some embodiments, when the thickness is 0.7 mm, the transmittance of the chemically strengthened crystallized glass for light with a wavelength of 550 nm may be 85.00% to 89.00%, 85.00% to 96.00%, 85.00% to 90.00%, 88.00% to 95.00%, 88.00% to 96.00%, 88.00% to 99.00%, 86.00%, 87.00%, 88.00%, 89.00%, 90.00%, 91.00%, 92.00%, 93.00%, 94.00%, 95.00%, 96.00%, etc., and all ranges and subranges between the above values. Note that in the embodiments, any of the above ranges may be combined with any other range.
[0080] In some embodiments of the present invention, a gemstone mineral hardness tester with Mohs hardness level 7 is fixed at a 45° angle using an electric pencil hardness tester, and the surface of the reinforced crystallized glass is scratched with a load of 750 g. The scratched crystallized glass is observed under a microscope at 400x magnification, and the surface of the reinforced crystallized glass is found to be free of scratches.
[0081] It should be noted that after the chemical strengthening ion exchange process, the composition of the surface of the crystallized glass may be different from that of the freshly formed crystallized glass (i.e., the crystallized glass for chemical strengthening that has not been subjected to ion exchange). However, in an embodiment, the composition of the crystallized glass at the center of the depth of the glass product or near the center of the depth still has the composition of the freshly formed crystallized glass. That is, in the present invention, the composition of the tensile stress layer of the strengthened crystallized glass still has the composition of the crystallized glass for chemical strengthening.
[0082] In some embodiments of the present invention, the tensile stress layer of the strengthened glass-ceramics or the glass-ceramics for chemical strengthening contains, in terms of mass percentage of oxides, 30.00%≦SiO2<35.00%, Al2O3: 30.00%-40.00%, ZnO: 10.00%-12.00%, MgO: 2.00%-4.00%, ZrO2: 5.00%-7.00%, Na2O: 2.00%-9.00%, Li2O: 0-2.00%, and B2O3: 0-8.00%. At the same time, the components of the tensile stress layer of the strengthened glass-ceramics or the glass-ceramics for chemical strengthening are: (1)X=((Na2O+B2O3) / ZrO2) / Al2O3, X≧2.00; (2)Y=ln[(Na2O+B2O3) / ZrO2], Y≧0; (3)Z=(SiO2+Al2O3-MgO-ZnO) / (Li2O+Na2O+B2O3), 4.00≦Z≦10.00; In the formulas (1) to (3), oxide represents the mass percentage of the oxide component; Meet the following.
[0083] Optionally, the tensile stress layer of the strengthened crystallized glass or the component of the chemically strengthened crystallized glass further comprises: (4)W=(0.8×(Al2O3-SiO2)+1.5×(ZnO-MgO)) / ZrO2, 0≦W≦3.00; In formula (4), oxide represents the mass percentage of the oxide component; Meet the following.
[0084] In some embodiments of the present invention, in the tensile stress layer of the strengthened crystallized glass or the crystallized glass for chemical strengthening, the mass percentage of SiO2 is 32.00% to 34.95%, and / or the mass percentage of Al2O3 is 32.00% to 38.00%, and / or ZnO is 10.00% to 11.48%, and / or MgO is 2.50% to 3.50%, and / or ZrO2 is 5.40% to 6.50%, and / or Na2O is 2.50% to 8.50%, and / or B2O3 is 2.50 to 8.00%.
[0085] In some embodiments of the present invention, the tensile stress layer of the strengthened glass-ceramics or the glass-ceramics for chemical strengthening further contains 0 to 3.00 wt % BaO and / or 0 to 2.00 wt % Y2O3.
[0086] In some embodiments of the present invention, the strengthened glass-ceramics or the chemically strengthened glass-ceramics is essentially free of TiO2 and P2O5.
[0087] The present invention optimizes the composition of the crystallized glass for chemical strengthening, and adjusts the relationship between each oxide and the content of each oxide in the composition system. As a result of examining each oxide component of the crystallized glass for chemical strengthening, the present invention has found that there is a certain correlation between each oxide component, and this correlation affects the structure and performance of the crystallized glass for chemical strengthening, and is related to the scratch resistance of the crystallized glass required for the present invention, as well as other performances of the crystallized glass.
[0088] According to the inventors' investigation, aluminum oxide has an extremely high dissociation energy G = 134 KJ cm -3Therefore, by increasing the content of Al2O3 in the spinel crystallized glass compounding system, the alumina saturation of the crystal phase can be increased, while the dissociation energy of the residual glass phase can be improved, which is advantageous for improving the intrinsic strength of the residual glass phase; and the atomic stacking density of glass increases with an increase in the coordination number of aluminum, and it has been found that increasing the content of Al2O3 is advantageous for improving the compactness of the crystallized glass system. However, when aluminum oxide is used instead of silicon oxide, it becomes more difficult to melt and mold the glass, and it is necessary to add components having a fluxing effect, such as alkali metal oxides, alkaline earth metal oxides, and boron oxide. Alkali metal oxides provide alkali metal ions to realize the toughening of the crystallized glass by chemical strengthening, and also provide free oxygen to affect the network structure of the glass. Although boron oxide has a good fluxing effect, the coordination structure of boron oxide is affected by the free oxygen provided by alkali metals and / or alkaline earth metals. If the content of boron oxide is too high, the proportion of boron-oxygen tetrahedra and boron-oxygen triangles in the glass phase will decrease, and part of the glass phase will change from the original cage structure in three-dimensional space to a layer structure in two-dimensional space, weakening the glass network structure. At the same time, if the content of boron oxide is too high, it will have a negative effect on the optical properties of the glass. Zinc oxide, magnesium oxide and aluminum oxide are the compositional components of the desired main crystalline phase ((Zn,Mg)Al2O4), and ZrO2 is a nucleating agent. The relationship between the contents of these oxides not only determines the content of the main crystalline phase in chemically strengthened glass-ceramics, but also determines the structure and inherent strength of the residual glass phase in chemically strengthened glass-ceramics.
[0089] Based on this, the present invention unintentionally found that the difficulty of melting the base glass and the heat treatment temperature when manufacturing the target chemically strengthened glass-ceramics using the base glass can be reduced by adjusting the glass-ceramics blend system based on the dosage range of each oxide. The glass blend provided by the present invention can be mass-produced by normal continuous melting, rolling, or other methods to obtain the base glass, thereby ensuring the moldability of the glass. And, when the heat treatment temperature of the base glass corresponding to the glass blend according to the present invention is 800°C or less, it is possible to obtain transparent chemically strengthened glass-ceramics having good optical properties with a zinc-magnesium spinel solid solution as the main crystal phase. Compared with the prior art, the blend system provided by the present invention can obviously reduce the heat treatment temperature, further reduce the difficulty of mass-producing spinel glass-ceramics, and improve the mass productivity of spinel glass-ceramics. Meanwhile, the synergistic effect of each oxide component at a specific content allows the target main crystal phase (Zn,Mg)Al2O4 with the desired content to be obtained, and the inherent strength of the residual glass phase in the chemically strengthened glass-ceramics is improved. By combining the main crystal phase (Zn,Mg)Al2O4 with high Young's modulus and shear modulus with the residual glass phase with high intrinsic strength, the resulting chemically strengthened glass-ceramics has high intrinsic strength and is superior in scratch resistance to conventional spinel-based glass-ceramics. The scratch resistance of the strengthened glass-ceramics obtained by strengthening the chemically strengthened glass-ceramics of the present invention is comparable to that of sapphire glass, and can meet the requirements for cover glass of high-end electronic products.
[0090] SiO2 is a glass network forming oxide and is an essential component for forming a glass network structure. If the content of SiO2 is appropriately increased, the stability and mechanical strength of the glass can be increased, but excessive SiO2 increases the viscosity of the substrate glass, making it more difficult to melt the glass, thereby reducing the formability of the substrate glass. In the present invention, the mass percentage of SiO2 is 30.00% to 35.00%, which is advantageous for improving the stability, formability and mechanical strength performance of the glass in a well-balanced manner. In some embodiments, the SiO2 content may be 30.00%-31.00%, 30.00%-32.00%, 30.00%-33.00%, 32.00%-34.95%, 31.00%-34.95%, 31.00%-34.00%, 30.00%, 30.50%, 31.00%, 31.50%, 32.00%, 32.50%, 33.00%, 33.50%, 34.00%, 34.50%, 34.95%, etc., and all ranges and subranges therebetween. It is to be noted that any of the above ranges may be combined with any other range in the embodiments.
[0091] Al2O3 is an intermediate oxide during glass formation, which can improve the chemical stability of glass. Al2O3 is one of the components that form the zinc magnesium spinel crystal phase after the crystallization of the substrate glass, and directly affects the content of the main crystal phase (Zn, Mg)Al2O4. At the same time, [AlO4] has a larger volume than [SiO4], so it can provide a larger space for ion exchange and promote the progress of chemical strengthening. And Al2O3 has a significant effect on the intrinsic strength of the residual glass phase due to its extremely high dissociation energy. However, excessive Al2O3 increases the viscosity of the substrate glass, which reduces the formability of the substrate glass. In the present invention, the mass percentage of Al2O3 is 30.00 to 40.00%. In some embodiments, the Al2O3 content is between 30.00% and 31.00%, between 30.00% and 32.00%, between 30.00% and 33.00%, between 32.00% and 35.00%, between 31.00% and 35.00%, between 31.00% and 34.00%, between 33.00% and 36.00%, between 32.00% and 38.00%, between 30.00% and 35. 00%, 34.00%-39.00%, 35.00%-40.00%, 36.00%-40.00%, 30.00%, 31.00%, 32.00%, 33.00%, 34.00%, 35.00%, 37.00%, 38.00%, 39.00%, 40.00%, etc., and all ranges and subranges therebetween. It is to be noted that in the embodiments, any of the above ranges may be combined with any other range.
[0092] ZnO provides the zinc necessary to form a zinc magnesium spinel crystal phase after crystallization of the substrate glass. ZnO can reduce the thermal expansion coefficient of the glass and increase the chemical stability, thermal stability and refractive index of the glass. In the present invention, the mass percentage of ZnO is 10% to 12%. In some embodiments, the content of ZnO can be 10.00% to 11.00%, 10.00% to 11.40%, 11.00% to 12.00%, 11.50% to 12.00%, 10.00%, 10.50%, 11.00%, 11.48%, 11.50%, 12.00%, etc., and all ranges and subranges therebetween. It is to be noted that in the embodiments, any of the above ranges can be combined with any other range.
[0093] MgO provides the magnesium necessary for the substrate glass to crystallize and form a zinc magnesium spinel crystal phase. MgO can slow down the hardening rate of the glass and improve the forming performance of the glass. MgO can further reduce the crystallization tendency and crystallization rate, increase the high temperature viscosity of the glass, and improve the chemical stability and mechanical strength of the glass. In the present invention, the mass percentage of MgO is 2% to 4%. In some embodiments, the content of MgO may be 2.00% to 3.00%, 3.00% to 4.00%, 2.00% to 2.50%, 2.50% to 3.00%, 2.50% to 4.00%, 3.50% to 4.00%, 2.00%, 2.50%, 3.00%, 3.50%, 4.00%, etc., and all ranges and subranges therebetween. It is to be noted that in the embodiments, any of the above ranges may be combined with any other range.
[0094] ZrO2 has a high cationic charge and a strong electric field strength, which brings about a large accumulation effect in the glass structure and functions as a nucleating agent in the substrate glass. At the same time, ZrO2 can further increase the strength and toughness of the crystallized glass and improve the corrosion resistance against acids and alkalis. In addition, ZrO2 is the second crystal phase of the crystallized glass in the system. However, since the melting of ZrO2 is extremely difficult, excessive ZrO2 cannot be uniformly dispersed in the substrate glass, and melting defects such as unmelted matter and precipitation are easily generated. In the present invention, the mass percentage of ZrO2 is 5% to 7%. In some embodiments, the ZrO2 content may be 5.00%-6.00%, 5.50%-6.00%, 5.50%-7.00%, 6.00%-7.00%, 6.50%-7.00%, 5.00%, 5.40%, 5.50%, 6.00%, 6.50%, 7.00%, etc., and all ranges and subranges therebetween, including any of the above ranges, which may be combined with any other range in any embodiment.
[0095] The tensile stress layer of the strengthened crystallized glass or the crystallized glass for chemical strengthening according to the present invention contains one or more kinds of alkali metal oxides, such as Li2O and Na2O, both of which can promote the chemical strengthening of the crystallized glass by the ion exchange process and improve the mechanical strength properties of the crystallized glass. At the same time, the alkali metal oxides, as network modifier oxides during glass formation, provide free oxygen, destroy the network structure of the glass, and further affect the inherent strength of the glass. However, destroying the network structure of the glass is advantageous to reduce the high-temperature viscosity of the glass and promote the melting and clarification of the glass liquid.
[0096] To balance various influences and ensure that the crystallized glass meets the desired performance, in the present invention, the mass percentage of Na2O is 2.00% to 9.00%. + is an ion exchange component necessary for chemical strengthening processes, and K + and Na, which has a small ionic radius in glass-ceramics. +By carrying out an exchange reaction with Na2O, a surface compressive stress is generated on the surface of the crystallized glass, which can further improve the strength and scratch resistance of the crystallized glass. In some embodiments, the content of Na2O may be 2.00% to 3.00%, 2.00% to 5.00%, 2.00% to 8.00%, 2.50% to 8.50%, 3.00% to 6.00%, 4.00% to 9.00%, 2.00% to 7.00%, 5.00% to 8.00%, 6.00% to 9.00%, 2.00%, 2.50%, 3.00%, 4.00%, 5.00%, 6.00%, 7.00%, 8.00%, 8.50%, 9.00%, etc., and all ranges and subranges therebetween. Note that in the embodiments, any of the above ranges may be combined with any other range.
[0097] In the present invention, the mass percentage of Li2O is 0.00% to 2.00%. + and the small ionic radius of Li in glass-ceramics. + The exchange reaction between Li2O and LiO2 forms deep stress in the crystallized glass, improving the strength and scratch resistance of the crystallized glass, and improving the impact resistance of the crystallized glass. In some embodiments, the content of Li2O may be 0.00-1.00%, 0.00-1.50%, 1.00%-1.50%, 1.00%-2.00%, 1.50%-2.00%, 0.00%, 1.00%, 1.50%, 2.00%, etc., and all ranges and subranges therebetween. Note that in the embodiments, any of the above ranges may be combined with any other range.
[0098] B2O3 functions as a flux in the glass formation process. The free oxygen provided by alkali metals or alkaline earth metals affects the coordination of boron oxide, transforming the boron oxide from a boron-oxygen triangle to a boron-oxygen tetrahedron composed of bridging oxygen, changing a part of the glass phase from the original layer structure in two-dimensional space to a cage structure in three-dimensional space, and reinforcing the glass network structure. B2O3 can reduce the high-temperature viscosity of glass, accelerate the fining of glass, reduce the crystallization ability of glass, and effectively alleviate the problem of the difficulty of melting the base glass caused by high content of aluminum oxide, but excessive B2O3 will reduce the chemical stability and mechanical strength of glass, affecting the optical properties of glass. In the present invention, the mass percentage of B2O3 is 0-8%. In some embodiments, the content of B2O3 may be 1.00%-6.00%, 2.00%-3.00%, 1.00%-4.00%, 1.00%-5.00%, 2.00%-5.00%, 2.50%-8.00%, 3.00%-6.00%, 4.00%-9.00%, 2.00%-7.00%, 5.00%-8.00%, 6.00%-9.00%, 0.00%, 1.00%, 2.00%, 2.50%, 3.00%, 4.00%, 5.00%, 6.00%, 7.00%, 8.00%, etc., and all ranges and subranges therebetween. Note that any of the above ranges may be combined with any other range in the embodiments.
[0099] In some embodiments, the value of X=((Na2O+B2O3) / ZrO2) / Al2O3 can be from 2.00 to 3.00, from 2.00 to 4.00, from 2.00 to 5.00, from 2.00 to 6.00, from 2.00 to 7.00, from 2.00 to 8.00, from 2.00 to 9.00, from 2.00 to 10.00, from 3.00 to 4.00, from 3.00 to 6.00, from 3.00 to 9.00, from 5.00 to 9.00, from 6.00 to 9.00, from 8.00 to 9.00, from 2.00, 3.00, 4.00, 5.00, 6.00, 7.00, 8.00, 9.00, 10.00, etc., and all ranges and subranges therebetween. It should be noted that in the embodiments, any of the above ranges can be combined with any other range.
[0100] In some embodiments, the value of Y=ln[(Na2O+B2O3) / ZrO2] may be 0.00-0.10, 0.00-1.00, 0.00-0.30, 0.00-0.60, 0.00-0.90, 0.00-0.40, 0.10-0.90, 0.30-0.70, 0.30-0.90, 0.20-0.50, 0.40-0.80, 0.10, 0.20, 0.30, 0.40, 0.50, 0.60, 0.70, 0.80, 0.90, 1.00, 1.10, etc., and all ranges and subranges therebetween. Note that in the embodiments, any of the above ranges may be combined with any other range.
[0101] In some embodiments, the value of Z=(SiO2+Al2O3-MgO-ZnO) / (Li2O+Na2O+B2O3) is 4.00-10.00, 4.00-5.00, 4.00-6.00, 4.00-7.00, 4.00-8.00, 4.00-9.00, 5.00-6.00, 5.00-7.00, 5.00-8.00, 5.00-9.00, 5.00-10.00, 6.00-10.00, 7.00-10.00, 8.00-10.00, 9.00-10.00, 10.00-10.00, 11.00-12.00, 13.00-14.00, 15.00-16.00, 17.00-18.00, 19.00-19.00, 20.00-21.00, 22.00-23.00, 23.00-24.00, 24.00-25.00, 25.00-26.00, 26.00-27.00, 27.00-28.00, 28.00-29.00, 29.00-30.00, 30.00-31.00, 31.00-32.00, 32.00-33.00, 33.00-34.00, 34.00-35.00, 35.00-36.00, 36.00-37.00, 37.00-38.00, 0.00-7.00, 6.00-8.00, 6.00-9.00, 6.00-10.00, 7.00-8.00, 7.00-9.00, 7.00-10.00, 8.00-9.00, 8.00-10.00, 9.00-10.00, 4.00, 5.00, 6.00, 7.00, 8.00, 9.00, 10.00, etc., and all ranges and subranges therebetween. It is to be noted that in the embodiments, any of the above ranges may be combined with any other range.
[0102] In some embodiments of the present invention, the content of each oxide in the tensile stress layer of the strengthened crystallized glass or the crystallized glass for chemical strengthening is further (4)W=(0.8×(Al2O3-SiO2)+1.5×(ZnO-MgO)) / ZrO2, 0≦W≦3.00; Meet the requirements. In formula (4), oxide represents the mass percentage of the oxide component. By adjusting the relationship of the contents of Al2O3, SiO2, ZnO, MgO, and ZrO2 to satisfy formula (4) while satisfying the range of each oxide and the requirements of formulas (1) to (3), it is possible to ensure that the transparent crystallized glass has excellent optical properties.
[0103] In some embodiments, the value of W=(0.8×(Al2O3-SiO2)+1.5×(ZnO-MgO)) / ZrO2 may be 0.00-3.00, 0.00-1.00, 0.00-2.00, 1.00-2.00, 1.00-3.00, 2.00-3.00, 0.00-0.50, 0.00-1.50, 0.00-2.50, 1.00-1.50, 1.00-2.50, 2.00-2.50, 2.5.00-3.00, 0.00, 0.50, 1.00, 1.50, 2.00, 2.50, 3.00, etc., and all ranges and subranges therebetween. Note that any of the above ranges may be combined with any other range in the embodiments. In some embodiments of the present invention, the strengthened glass-ceramics is obtained by subjecting chemically strengthened glass-ceramics to a chemical strengthening treatment.
[0104] In some embodiments of the present invention, in the molar percentage of oxides in the chemically strengthened glass-ceramics, the molar percentage of Al2O3 is greater than the sum of the molar percentages of MgO and ZnO, the theoretical crystallinity of the chemically strengthened glass-ceramics is at least 30.00wt% or more, and optionally 30.00wt% to 50.00wt%. When the chemically strengthened glass-ceramics satisfies the theoretical crystallinity, the dissociation energy U per unit volume of the residual glass phase in the chemically strengthened glass-ceramics is 71.00KJ cm -3 or more, and selectively 71.00 KJ cm -3 ~134.00KJ cm -3 It is.
[0105] In some embodiments, the theoretical crystallinity of the chemically strengthened crystallized glass may be 30.00wt%-40.00wt%, 30.00wt%-60.00wt%, 30.00wt%-70.00wt%, 35.00wt%-45.00wt%, 32.00wt%-48.00wt%, 41.00wt%-49.00wt%, 30.00wt%, 35.00wt%, 40.00wt%, 45.00wt%, 50.00wt%, etc., and all ranges and subranges therebetween. Note that in the embodiments, any of the above ranges may be combined with any other range.
[0106] The theoretical crystallinity refers to the theoretically highest degree of crystallization when a certain composition of base glass forms a specific crystal phase. The theoretical crystallinity is the theoretically highest crystallinity, and is an important parameter for reliably obtaining crystallized glass having the desired crystal phase in the required content by performing preliminary basic control of the main crystal phase components.
[0107] Since the crystal phase and the degree of crystallization of different systems of crystallized glass are different, the calculation method of the theoretical degree of crystallization is also different. The theoretical degree of crystallization of different crystallized glass systems is determined by two parts, for example, a nucleating agent such as ZrO2 in its components and an oxide constituting a specific crystal phase. In the present invention, the main crystal phase of the chemically strengthened crystallized glass is a zinc magnesium spinel solid solution (Zn, Mg) Al2O4, and the secondary crystal phase includes one or more kinds selected from tetragonal ZrO2, Zn2SiO4, and Mg2SiO4. Therefore, the theoretical degree of crystallization of the crystallized glass according to the present invention is determined by two parts, for example, a nucleating agent such as ZrO2 in its components and an oxide Al2O3, MgO, and ZnO constituting the crystal phase.
[0108] The main crystalline phase of the chemically strengthened glass-ceramics according to the present invention is zinc magnesium spinel solid solution (Zn,Mg)Al2O4, and the composition of the crystalline phase is expressed in terms of mole percentage of oxides, MgO / Al2O3=1 in MgAl2O4, and ZnO / Al2O3=1 in ZnAl2O4. In order to obtain high crystallinity and good strengthening effect, it is required that a part of Al2O3 remains in the residual glass phase after ZnAl2O4 and / or MgAl2O4 are completely formed. Since the [AlO4] tetrahedron has a larger volume than the [SiO4] tetrahedron, an appropriate amount of Al2O3 remains in the residual glass phase, which provides a larger space for ion exchange in the chemical strengthening process and can promote the progress of ion exchange. Moreover, in the chemically strengthened glass-ceramics according to the present invention, the mole percentage of Al2O3 is greater than the sum of the mole percentages of ZnO and MgO.
[0109] In some embodiments of the present invention, when the chemically strengthened glass-ceramics meets the theoretical crystallinity, the dissociation energy U per unit volume of the residual glass phase in the chemically strengthened glass-ceramics is 71.00 kJ cm -3 or more, and selectively 71.00KJ cm -3 ~134.00kJ cm -3 In some embodiments, the dissociation energy U per unit volume of the residual glass phase in the chemically strengthened glass-ceramics is 71.00 KJ cm -3 ~75.00KJ cm -3 , 71.00 KJ cm -3 ~80.00KJ cm -3 , 71.00 KJ cm -3 ~90.00KJ cm -3 , 71.00 KJ cm -3 ~100.00KJ cm -3 , 71.00 KJ cm -3 ~110.00KJ cm -3 , 71.00 KJ cm -3 ~120.00KJ cm -3 , 71.00 KJ cm -3 ~130.00KJ cm -3 , 80.00KJ cm -3~90.00KJ cm -3 , 80.00KJ cm -3 ~100.00KJ cm -3 , 80.00KJ cm -3 ~110.00KJ cm -3 , 80.00KJ cm -3 ~120.00KJ cm -3 , 80.00KJ cm -3 ~130.00KJ cm -3 , 90.00KJ cm -3 ~100.00KJ cm -3 , 90.00KJ cm -3 ~110.00KJ cm -3 , 90.00KJ cm -3 ~120.00KJ cm -3 , 90.00KJ cm -3 ~130.00KJ cm -3 , 100.00KJ cm -3 ~110.00KJ cm -3 , 100.00KJ cm -3 ~120.00KJ cm -3 , 100.00KJ cm -3 ~130.00KJ cm -3 , 71.00 KJ cm -3 , 80.00KJ cm -3 , 90.00KJ cm -3 , 100.00KJ cm -3 , 110.00KJ cm -3 , 120.00KJ cm -3 , 134.00KJ cm -3 and so forth, and all ranges and subranges between the above values. It should be noted that in practice, any of the above ranges can be combined with any other range.
[0110] The calculation of the dissociation energy U per unit volume of the residual glass phase will be described below by taking the spinel-based crystallized glass according to the present invention as an example.
[0111] In the glass formulation, assuming that the molar percentage of Al2O3 is a, the molar percentage of ZnO is b, and the molar percentage of MgO is c, then a>b+c. After producing a zinc magnesium spinel crystallized glass having a theoretical crystallinity from the base glass of the formulation, the dissociation energy U per unit volume of the residual glass phase is calculated as follows:
[0112] 1. Determine the mole percentages of ZnO, MgO, and Al2O3 in the residual glass phase.
[0113] This is the theoretical crystallinity, that is, the crystallinity reached when both ZnO and MgO are involved in the precipitation of spinel, so ZnO and MgO are all present in the crystal phase, that is, the content of ZnO and MgO in the residual glass phase is 0. Since a>b+c, Al2O3 (a-(b+c)) remains in the residual glass phase, and the molar percentage of Al2O3 in the residual glass phase is calculated according to the content of each oxide in the residual glass phase.
[0114] 2. Determine the mole percentage of other oxides in the residual glass phase, except Al2O3, ZnO, and MgO.
[0115] (1) Nucleating agents generally precipitate before crystals. For example, in the case of ZrO2, a nucleating agent, minute crystal grains less than 1 nm in size are precipitated in the nucleation step of crystallized glass, and crystals grow on them. In the case of TiO2, a nucleating agent, titanate crystal nuclei are formed in the nucleation step of crystallized glass, and under their guidance, crystals grow and cover them. Since nucleating agents are generally located in the center of crystals, theoretically, all of the nucleating agent is present in the crystal phase, and the content of nucleating agent in the remaining glass phase is zero.
[0116] (2) Except for the oxides constituting the crystal phase and the nucleating agent, the other oxides in the base glass are theoretically present in the residual glass phase. The mole percentages of the other oxides in the residual glass phase are calculated based on the content of each oxide in the residual glass phase.
[0117] 3. In the residual glass phase, the mole percentage of a certain oxide is defined as n i and the dissociation energy coefficient of the oxide is defined as U i If we define it as U i The values of can be obtained as shown in Table 1 below.
[0118] If the dissociation energy per unit volume of the residual glass phase is defined as U, then (Formula 1) U=ΣU i ×n i U i is the dissociation energy coefficient, with units of kJ cm -3 and n i is the mole percentage of a given oxide in the residual glass phase.
[0119] [Table 1]
[0120] In some embodiments of the present invention, the tensile stress layer of the strengthened glass-ceramics or the glass-ceramics for chemical strengthening further contains 0 to 3.00 wt % BaO and / or 0 to 2.00 wt % Y2O3.
[0121] Y2O3, as a cation of high electric field strength, is advantageous in cooperation with Al2O3 to increase the atomic deposition density of glass, and is also advantageous in improving the hardness and Young's modulus of crystallized glass. In the present invention, the mass percentage of Y2O3 is 0.00-2.00%. In some embodiments, the content of Y2O3 may be 0.00-1.00%, 0.00-1.50%, 1.00%-1.50%, 1.00%-2.00%, 1.50%-2.00%, 0.00, 1.00%, 1.50%, 2.00%, etc., and all ranges and subranges therebetween. Note that in the embodiments, any of the above ranges may be combined with any other range.
[0122] BaO has a good fluxing effect, and the effect is particularly remarkable in this system. At the same time, BaO increases the refractive index of the glass phase, and can improve the optical properties of the glass. In the present invention, the mass percentage of BaO is 0 to 3.00%. In some embodiments, the BaO content may be 0.00-3.00, 0.00-1.00, 0.00-2.00, 1.00-2.00, 1.00-3.00, 2.00-3.00, 0.00-0.50, 0.00-1.50, 0.00-2.50, 1.00-1.50, 1.00-2.50, 2.00-2.50, 2.5.00-3.00, 0.00, 0.50, 1.00, 1.50, 2.00, 2.50, 3.00, etc., and all ranges and subranges therebetween, including any of the above ranges, in any embodiment, and any of the above ranges may be combined with any other range.
[0123] In some embodiments of the present invention, the strengthened crystallized glass or the chemically strengthened crystallized glass is essentially free of TiO2 and / or P2O5. Here, "essentially free" means that TiO2 and / or P2O5 are not actively added or blended into the glass, but may be present in small amounts as contaminants. The inventors have found that adding TiO2 to the blend of the present invention results in undesirable color. In order to obtain the desired transparent crystallized glass, TiO2 is selectively free of the blend.
[0124] In the present invention, the chemically strengthened crystallized glass is produced by the following method.
[0125] Step 1: obtaining a substrate glass, the substrate glass containing, in terms of mass percentage of oxides, the following components: 30.00%≦SiO2<35.00%, Al2O3: 30.00% to 40.00%, ZnO: 10.00% to 12.00%, MgO: 2.00% to 4.00%, ZrO2: 5.00% to 7.00%, Na2O: 2.00% to 9.00%, Li2O: 0 to 2.00%, and B2O3: 0 to 8.00%, wherein the content of each oxide in the substrate glass is further (1)X=((Na2O+B2O3) / ZrO2) / Al2O3, X≧2.00; (2)Y=ln[(Na2O+B2O3) / ZrO2], Y≧0; (3)Z=(SiO2+Al2O3-MgO-ZnO) / (Li2O+Na2O+B2O3), 4.00≦Z≦10.00; In the formulas (1) to (3), oxide represents the mass percentage of the oxide component; Meet the following.
[0126] Step 2: The substrate glass is subjected to a heat treatment to obtain the chemically strengthened crystallized glass, and the heat treatment includes a nucleation treatment and / or a crystallization treatment. When the substrate glass is subjected to a heat treatment, a single-stage heat treatment, a two-stage or multi-stage heat treatment may be performed. A single-stage heat treatment means that a nucleation treatment is not performed separately, and nucleation and the target crystal growth are performed directly in a single-stage heating process, and is understood to be a direct crystallization treatment. A two-stage heat treatment means that a two-stage heating process is performed, first a nucleation treatment, i.e., a nucleation treatment, and then a target crystal growth treatment, i.e., a crystallization treatment.
[0127] The substrate glass has the composition, in terms of mass percentage of oxides, of the crystallized glass for chemical strengthening.
[0128] Optionally, in step 2, when nucleation treatment is performed, the nucleation temperature is 650°C to 850°C, optionally 650°C to 750°C, and the nucleation treatment time is 0 to 72 hours, optionally 0 to 24 hours.
[0129] Optionally, in step 2, when the crystallization treatment is performed, the crystallization temperature is 700° C. to 1000° C., optionally 700° C. to 850° C., and the crystallization treatment time is 0.1 to 72 hours, optionally 0.1 to 24 hours.
[0130] Optionally, in step 2, when performing the heat treatment, the temperature rise rate is controlled to 5 to 30° C. / min, and optionally to 5 to 15° C. / min.
[0131] Optionally, the content of each oxide in the substrate glass may further include: (4)W=(0.8×(Al2O3-SiO2)+1.5×(ZnO-MgO)) / ZrO2,0≦W≦3.00; In formula (4), oxide represents the mass percentage of the oxide component; Meet the following.
[0132] Optionally, the substrate glass further contains 0 to 3.00 wt % BaO and / or 0 to 2.00 wt % Y2O3.
[0133] Optionally, the substrate glass is essentially free of TiO2 and / or P2O5.
[0134] In the present invention, the method of forming the substrate glass includes, but is not limited to, a float method, overflow, rolling, or casting process. Exemplarily, the components are mixed uniformly according to the formulation, melted and molded, and then cooled and annealed to obtain the substrate glass. For example, the substrate glass raw material is melted at a melting temperature of 1480°C to 1650°C, the molten glass liquid is molded, and the molded product is cooled and annealed to obtain the substrate glass. Optionally, the annealing temperature is 500°C to 650°C, and the annealing is performed for 12 to 48 hours.
[0135] In the present invention, when manufacturing the substrate glass, a fining agent may be added to the manufacturing raw material of the substrate glass, and the fining agent includes one or more of NaCl, Na2SO4, SnO2, As2O3, Sb2O3, NaNO3, KNO3, CeO2 and (NH4)2SO4, and optionally includes one or more of NaCl, SnO2, NaNO3 and CeO2, but is not limited thereto. Based on the total mass of the raw material of the substrate glass, the amount of the fining agent added is 0.01wt% to 2.00wt%, and optionally 0.01wt% to 1.50wt%.
[0136] In some embodiments of the present invention, the chemically strengthened crystallized glass is subjected to chemical strengthening treatment by placing the crystallized glass for chemical strengthening in a salt bath containing potassium salt at 380°C to 550°C, the chemical strengthening treatment time being 1h to 96h, optionally 1h to 48h, to obtain the strengthened crystallized glass, the potassium salt including one or more selected from potassium nitrate, potassium sulfate, and potassium carbonate, optionally potassium nitrate.
[0137] In some embodiments, the salt bath containing potassium salt is 100 wt% potassium salt, optionally 100 wt% potassium nitrate, or may be a mixed salt of potassium salt and sodium salt, optionally a mixed salt of potassium nitrate and sodium nitrate. The salt bath may further contain 0-1 wt% lithium salt, optionally 0-1 wt% lithium nitrate. When performing chemical strengthening treatment, one-stage chemical strengthening may be performed, or two-stage or multi-stage chemical strengthening may be performed.
[0138] In some embodiments, the duration of the chemical strengthening treatment is 1.00h to 5.00h, 1.00h to 6.00h, 3.00h to 10.00h, 5.00h to 10.00h, 7.00h to 12.00h, 9.00h to 24.00h, 12.00h to 36.00h, 24.00h to 44.00h, 8.00h to 24.00h, 9.00h to 44.00h, 25.00h to 36.00h, 26.00h to 28.00h, 28.00h to 36.00h, 29.00h to 44.00h, 30.00h to 30.00h, 31.00h to 31.00h, 32.00h to 32.00h, 33.00h to 34.00h, 34.00h to 35.00h, 35.00h to 36.00h, 36.00h to 37.00h, 37.00h to 38.00h, 38.00h to 39.00h, 39.00h to 4 ... h, 22.00h-37.00h, 48.00h-96.00h, 6.00h, 8.00h, 12.00h, 14.00h, 24.00h, 32.00h, 36.00h, 22.00h, 18.00h, 28.00h, 42.00h, 48.00h, 60h, 65h, 70h, 80h, 90h, 96h, etc., and all ranges and subranges between the above values.
[0139] In some embodiments, the temperature of the salt bath used in the chemical strengthening process may be 380°C-400°C, 400°C-450°C, 450°C-500°C, 500°C-550°C, 400°C-420°C, 450°C, 480°C, 500°C, 510°C, 530°C, 540°C, 550°C, etc., and all ranges and subranges therebetween.
[0140] Third, the present invention further provides a glassware produced from the above-mentioned strengthened crystallized glass or the above-mentioned chemically strengthened crystallized glass.
[0141] The glassware of the present invention may be regular or irregular, and can be manufactured by those skilled in the art according to the requirements.
[0142] Fourth, the present invention further provides an electronic device comprising the above-mentioned strengthened glass-ceramics or the above-mentioned chemically strengthened glass-ceramics.
[0143] The electronic device according to the present invention includes at least one of a mobile phone, a display (e.g., an in-vehicle display, an in-vehicle display, etc.), a tablet, a digital wristwatch, a smart wearable terminal (e.g., a smart band, a smart watch, a smart glass), and a television, but is not limited to these. In the electronic device of the present invention, a layer may or may not be provided on the surface of the cover component.
[0144] Exemplarily, the electronic device provided by the present invention comprises: a case including a front surface, a back surface, and sides; an electronic component at least partially disposed within the case, the electronic component including at least a controller, a memory, and a display, the display being disposed on or adjacent to a front surface of the case; a covering substrate disposed above the display; Here, at least a portion of at least one of the case or the covering substrate contains any one of the above-mentioned chemically strengthening glass-ceramics or strengthened glass-ceramics.
[0145] The chemically strengthened crystallized glass and strengthened crystallized glass of the present invention have excellent properties and can be included / applied not only to other products but also to any product that requires a certain degree of transparency, scratch resistance or other combinations.
[0146] V. Specific Examples
[0147] Example S1:
[0148] (1) Manufacturing of substrate glass: According to the formula, a total mass of 1000g of raw materials was taken and mixed, and after uniform mixing for 30 minutes, 5g of NaCl was added as a fining agent. The resulting mixture was placed in a platinum crucible and melted at a temperature of 1650℃ for 5 hours, then poured into a mold to form and cool, cooled to 900℃, placed in an annealing furnace at 620℃ for 12 hours, and then cooled to room temperature to obtain the substrate glass.
[0149] (2) Production of crystallized glass (i.e., crystallized glass for chemical strengthening): The substrate glass is subjected to heat treatment, and the temperature is increased to a nucleation temperature of 690°C at a heating rate of 10°C / min, and the nucleation treatment time is 240 min. Then, the temperature is increased to a crystallization temperature of 760°C at a heating rate of 10°C / min, and the crystallization treatment time is 240 min. This results in a crystallized glass block. Here, the nucleation treatment time refers to the time for which the crystallization furnace is heated to a set nucleation temperature according to a set heating rate and then kept at the temperature. The crystallization treatment time refers to the time for which the crystallization furnace is heated to a set crystallization temperature according to a set heating rate and then kept at the temperature.
[0150] (3) Cold working treatment: The above crystallized glass block is subjected to a cold working treatment, which includes a shaping treatment and a slicing treatment, to obtain a crystallized glass piece of a desired size, for example, 50 mm in length x 50 mm in width x 0.7 mm in thickness.
[0151] After the slicing process, CNC processing, grinding processing, and polishing processing may be performed in sequence, or after the slicing process, at least one method from among CNC processing, grinding processing, and polishing processing may be selected to perform modification processing of the glass pieces.
[0152] In Example S1, the crystallized glass sample for measuring the physical property parameters of the crystallized glass and for chemical strengthening (ie, the crystallized glass piece for chemical strengthening) is a polished piece having a length of 50 mm, a width of 50 mm, and a thickness of 0.7 mm.
[0153] (4) Preparation of strengthened crystallized glass: The above-mentioned crystallized glass pieces for chemical strengthening are placed in 100 wt% KNO3 at 480°C to carry out one-stage chemical strengthening ion exchange, the strengthening time is 6 hours (i.e., 360 minutes), and thus strengthened crystallized glass is obtained.
[0154] Examples S2 to S10: Except for adjusting the component contents and related parameters as shown in Tables 2 and 4, respectively, the rest are the same as Example S1.
[0155] Comparative examples D1~D7: Except for adjusting the component contents and related parameters as shown in Tables 3 and 5, respectively, the rest are the same as Example S1.
[0156] Tables 2 to 7 show the formulation tables for the examples and comparative examples, the characteristic parameters of the chemically strengthened crystallized glass and the characteristic parameters of the strengthened crystallized glass for the examples and comparative examples, the scratch resistance experiment plan, and the scratch test results for the chemically strengthened crystallized glass and the strengthened crystallized glass for the examples and comparative examples.
[0157]
Table 2
[0158]
Table 3
[0159]
Table 4
[0160]
Table 5
[0161]
Table 6
[0162]
Table 7
[0163] As can be seen from the above results, the present invention strictly controls the content of each oxide in Examples S1 to S10, and adjusts the content of important oxides in X, Y, and Z, so that the obtained chemically strengthened crystallized glass has a high residual glass phase dissociation energy, and the desired spinel crystal of the present invention is formed in the chemically strengthened crystallized glass, while maintaining excellent optical properties. By combining the main crystal phase (Zn, Mg)Al2O4 having a high Young's modulus and shear modulus with the residual glass phase having a high intrinsic strength, the finally obtained chemically strengthened crystallized glass has a high intrinsic strength and has a better scratch resistance than conventional spinel-based crystallized glass. And, by strengthening the chemically strengthened crystallized glass to meet specific stress characteristics, the strengthened crystallized glass is given excellent surface stress characteristics and deep layer stress characteristics, and finally the mechanical properties of the strengthened crystallized glass according to the present invention are greatly improved, and the strengthened crystallized glass can achieve a scratch resistance effect comparable to that of sapphire glass.
[0164] The chemically strengthened crystallized glass of Example S1 of the present invention passed the scratch damage inspection by a load of 250g, 500g, gem mineral hardness scale No. 7 (Mohs hardness level 7) and a load of 750g, gem mineral hardness scale No. 6 (Mohs hardness level 6), and there were no scratches on the scratched crystallized glass surface. The scratch effect is shown in Figure 4.
[0165] The chemically strengthened crystallized glass of Examples S2 and S8 of the present invention passed the scratch test using a gemstone mineral hardness scale No. 7 (Mohs hardness level 7) under a load of 750g, and no scratches were found on the scratched crystallized glass surface. The scratch effect is shown in Figure 5.
[0166] As can be seen from Table 7 and Figs. 4 and 5, all of the chemically strengthened crystallized glasses according to the present invention have good scratch resistance.
[0167] The strengthened crystallized glass of Example S1 of the present invention can pass the scratch test using a gemstone mineral hardness scale No. 7 (Mohs hardness level 7) under a load of 750g, and there are no scratches on the scratched crystallized glass surface. The scratch effect is shown in FIG.
[0168] In the case of the reinforced crystallized glass of Examples S2 and S8 of the present invention, the scratching effect of the scratched crystallized glass surface is similar to that of sapphire glass measured under the same conditions in a scratching test using a gemstone mineral hardness scale No. 8 (Mohs hardness level 8) with a load of 750g. The scratching effect is shown in Figure 7. This shows that the scratch resistance effect of the reinforced crystallized glass of Examples S2 and S8 of the present invention is comparable to that of sapphire glass.
[0169] As can be seen from Table 7 and Figures 6 and 7, the use of the strengthened glass-ceramics obtained by strengthening the chemically strengthened glass-ceramics of the present invention has improved scratch resistance compared to that of the chemically strengthened glass-ceramics. The scratch resistance achieved by the strengthened glass-ceramics of the present invention is comparable to that of sapphire glass, and can meet the demand for cover glass of high-end electronic products.
[0170] Comparative Examples D1 to D7 did not fully meet the requirements of the glass blend of the present invention, and the stress characteristics after strengthening did not meet the requirements of the proposal of the present invention. The finally obtained crystallized glass for chemical strengthening and strengthened crystallized glass were all different from those of the present invention, and the scratch resistance was clearly inferior to that of the examples of the present invention.
[0171] The reinforced crystallized glass of the comparative examples D1 and D2 failed to pass the scratch test using a 750g load and a gemstone mineral hardness scale number 7 (Mohs hardness level 7), and all scratched crystallized glass had obvious scratches on the surface. The scratch effect is shown in Figure 8. Comparing the reinforced crystallized glass of D1 and D2, the scratch resistance of the reinforced crystallized glass of D1 is better than that of D2.
[0172] The dissociation energy per unit volume of the residual glass phase in comparative example D5 is relatively high, 75.46 kJ cm -3 However, in this proposal, the improvement of dissociation energy is due to the large amount of Li contained in the system. Through testing, the present invention has found that this proposal cannot obtain a transparent chemically strengthened crystallized glass sample by heat treatment.
[0173] Comparative Example D6 is a mainstream crystallized glass product in the current cover market. The chemically strengthened crystallized glass of Comparative Example D6 could not pass the scratch test by a load of 750g and a gemstone mineral hardness tester No. 6 (Mohs hardness level 6), and there were obvious scratches on the scratched crystallized glass surface, and the scratches were deep and wide, with fish scale patterns or scratch debris. The scratch effect is shown in Figure 9. The strengthened crystallized glass of Comparative Example D6 still could not pass the scratch test by a load of 750g and a gemstone mineral hardness tester No. 6 (Mohs hardness level 6), and there were obvious scratches on the scratched crystallized glass surface. The scratch effect is shown in Figure 10.
[0174] As can be seen from Table 7 and Figures 8 to 10, the scratch resistance of the chemically strengthened crystallized glass and strengthened crystallized glass of Comparative Examples D1 to D7 is clearly inferior to the scratch resistance of the chemically strengthened crystallized glass and strengthened crystallized glass of the present invention.
[0175] In addition, all the examples of the present invention have a lower heat treatment temperature than the comparative examples D1 to D5, so that the base glass obtained by the compounding system of the present invention has a zinc-magnesium spinel solid solution as the main crystalline phase when the heat treatment temperature is below 800 ° C., and can obtain transparent chemically strengthened crystallized glass with good optical properties. Compared with the prior art, the component system of the chemically strengthened crystallized glass provided by the present invention can obviously reduce the heat treatment temperature, and further reduce the difficulty of mass-producing spinel crystallized glass, improving the mass productivity of spinel crystallized glass. That is, it shows that the mass productivity of the chemically strengthened crystallized glass compounding system of the present invention is high. At the same time, the compounding system of the present invention contains a relatively small amount of lithium, so the raw material cost is much lower than the lithium aluminosilicate crystallized glass that is the mainstream in the market, and the future application is good.
[0176] Finally, the above embodiments are not intended to limit the technical solutions of the present invention, but are only used to explain the technical solutions of the present invention. Those skilled in the art can understand that any modifications or equivalent replacements of the technical solutions of the present invention that do not deviate from the spirit and scope of the present invention are included in the scope of the claims of the present invention.
Claims
1. A reinforced crystallized glass including a compressive stress layer and a tensile stress layer and having high scratch resistance, The main crystal phase of the strengthened glass-ceramics is (Zn, Mg)Al 2 O 4 and the strengthened crystallized glass contains Na 2 O is contained, and the surface K of the strengthened crystallized glass is 2 The O concentration is 7.00 wt % or more, and optionally 7.00 to 15.00 wt %; In the strengthened crystallized glass, a depth along a thickness direction of the glass from any surface of the strengthened crystallized glass to a position near the surface and having a potassium (K) concentration similar to that of the center of the strengthened crystallized glass is 0.07t or more, and optionally 0.07t to 0.10t, where t is the thickness of the strengthened crystallized glass. The present invention relates to a reinforced crystallized glass having high scratch resistance.
2. When the thickness is 0.7 mm, the single rod static pressure strength of the strengthened crystallized glass is 450N or more, and optionally 450-650N; 2. The strengthened crystallized glass having high scratch resistance according to claim 1.
3. The Young's modulus of the strengthened crystallized glass is 110 GPa or more, and optionally 110 to 140 GPa; 3. The strengthened crystallized glass having high scratch resistance according to claim 1 or 2.
4. The Vickers hardness of the strengthened crystallized glass is 750 kgf / mm 2 or more, and selectively 750 to 900 kgf / mm 2 and more selectively 800 to 900 kgf / mm 2 That is, 4. The strengthened crystallized glass having high scratch resistance according to claim 1.
5. In the strengthened crystallized glass, the average crystal grain size is 15.00 nm or less, optionally 1.00 to 10.00 nm, and further optionally 4.50 to 8.00 nm; and / or In the strengthened crystallized glass, the crystal content is 20.00 to 50.00 wt%, optionally 25.00 to 50.00 wt%, and further optionally 25.00 to 45.00 wt%; 5. The strengthened crystallized glass having high scratch resistance according to claim 1.
6. The secondary crystal phase of the strengthened crystallized glass is tetragonal ZrO 2 , Zn 2 SiO 4 , Mg 2 SiO 4 One or more selected from 6. The strengthened crystallized glass having high scratch resistance according to claim 1.
7. The reinforced crystallized glass is transparent within the visible light range; 7. The strengthened crystallized glass having high scratch resistance according to claim 1.
8. A gemstone mineral hardness tester having a Mohs hardness level of 7 was fixed at an angle of 45° using an automatic pencil hardness tester, and the surface of the strengthened crystallized glass was scratched with a load of 750 g. When the scratched crystallized glass was observed under a microscope at a magnification of 400, no scratches were found on the surface of the strengthened crystallized glass.
8. The strengthened crystallized glass having high scratch resistance according to claim 1.
9. In terms of mass percentage of oxides, the tensile stress layer of the strengthened crystallized glass has a content of 30.00%≦SiO 2 <35.00%, Al 2 O 3 : 30.00% to 40.00%, ZnO: 10.00% to 12.00%, MgO: 2.00% to 4.00%, ZrO 2 :5.00%~7.00%, Na 2 O: 2.00% to 9.00%, Li 2 O: 0 to 2.00%, and B 2 O 3 0 to 8.00%, and the components of the tensile stress layer of the strengthened crystallized glass are (1)X=((Na 2 O+B 2 O 3 ) / ZrO 2 ) / Al 2 O 3 、X≧2.00; (2)Y=ln[(Na 2 O+B 2 O 3 ) / ZrO 2 ]、Y≧0; (3)Z=(SiO 2 +AS 2 O 3 -MO-ZﻎO) / (L- 2 O+1 2 O+B 2 O 3 ),4.00≦Z≦10.00; In formulas (1) to (3), oxide represents the mass percentage of the oxide component; 9. The strengthened crystallized glass having high scratch resistance according to claim 1, which satisfies the following:
10. The components of the tensile stress layer of the strengthened crystallized glass further include (4)W=(0.8×(Al 2 O 3 -SiO 2 )+1.5×(ZnO-MgO)) / ZrO 2 ,0≦W≦3.00; In formula (4), the oxide represents the mass percentage of the oxide component.
10. The strengthened crystallized glass having high scratch resistance according to claim 1, which satisfies the above requirements.
11. In the tensile stress layer of the strengthened crystallized glass, SiO 2 and / or Al 2 O 3 and / or ZnO is 10.00% to 11.48% and / or MgO is 2.50% to 3.50% and / or ZrO 2 is 5.40% to 6.50%, and / or Na 2 O is 2.50% to 8.50%, and / or B 2 O 3 is 2.50 to 8.00%, 11. The strengthened crystallized glass having high scratch resistance according to claim 1.
12. The tensile stress layer of the strengthened crystallized glass further contains 0 to 3.00 wt % BaO and / or 0 to 2.00 wt % Y. 2 O 3 Including, 12. The strengthened crystallized glass having high scratch resistance according to claim 1.
13. The strengthened crystallized glass contains TiO 2 and P 2 O 5 Basically, it does not include 13. The strengthened crystallized glass having high scratch resistance according to claim 1.
14. The strengthened crystallized glass is obtained by subjecting a chemical strengthening treatment to a chemically strengthened crystallized glass, and specifically, The chemically strengthened crystallized glass is put into a salt bath containing potassium salt at 380°C to 550°C to perform chemical strengthening treatment, and the time of the chemical strengthening treatment is 1h to 96h, and optionally 1h to 48h, to obtain the strengthened crystallized glass, and the potassium salt includes one or more selected from potassium nitrate, potassium sulfate, and potassium carbonate, and optionally potassium nitrate.
14. The strengthened crystallized glass having high scratch resistance according to claim 1.
15. A chemically strengthened crystallized glass for producing the strengthened crystallized glass according to any one of claims 1 to 14, The main crystal phase of the chemically strengthened glass-ceramics is (Zn, Mg)Al 2 O 4 In the glass-ceramics for chemical strengthening, the oxide molar percentage is Al 2 O 3 is greater than the sum of the molar percentages of MgO and ZnO, the theoretical crystallinity of the chemically strengthened crystallized glass is at least 30.00 wt% or more, and optionally 30.00 wt% to 50.00 wt%. When the chemically strengthened crystallized glass satisfies the theoretical crystallinity, the dissociation energy U per unit volume of the residual glass phase in the chemically strengthened crystallized glass is 71.00 kJ cm -3 or more, and optionally 71.00 KJ cm -3 ~134.00kJ・cm -3 That is, 1. A chemically strengthened crystallized glass.
16. In terms of mass percentage of oxides, the glass-ceramics for chemical strengthening has a content of 30.00%≦SiO 2 <35.00%, Al 2 O 3 : 30.00% to 40.00%, ZnO: 10.00% to 12.00%, MgO: 2.00% to 4.00%, ZrO 2 :5.00%~7.00%, Na 2 O: 2.00% to 9.00%, Li 2 O: 0 to 2.00%, and B 2 O 3 0 to 8.00% and the components of the chemically strengthened crystallized glass are (1)X=((Na 2 O+B 2 O 3 ) / ZrO 2 ) / Al 2 O 3 、X≧2.00; (2)Y=ln[(Na 2 O+B 2 O 3 ) / ZrO 2 ]、Y≧0; (3)Z=(SiO 2 +AS 2 O 3 -MO-ZﻎO) / (L- 2 O+1 2 O+B 2 O 3 ),4.00≦Z≦10.00; In formulas (1) to (3), oxide represents the mass percentage of the oxide component; The chemically strengthened crystallized glass according to claim 15, which satisfies the above.
17. The components of the crystallized glass for chemical strengthening further include (4) W=(0.8×(Al 2 O 3 -SiO 2 )+1.5×(ZnO-MgO)) / ZrO 2 , 0≦W≦3.00; in formula (4), the oxide represents the mass percentage of the oxide component; and / or The Young's modulus of the chemically strengthened crystallized glass is 110 GPa or more, and optionally 110 to 140 GPa; and / or In the above-mentioned chemically strengthened crystallized glass, the average crystal grain size is 15.00 nm or less, optionally 1.00 to 10.00 nm, and further optionally 4.50 to 8.00 nm; and / or In the chemically strengthened crystallized glass, the crystal content is 20.00 to 50.00 wt%, optionally 25.00 to 50.00 wt%, and further optionally 25.00 to 45.00 wt%, and / or The secondary crystal phase of the chemically strengthened crystallized glass is tetragonal ZrO 2 , Zn 2 SiO 4 , Mg 2 SiO 4 and / or The chemically strengthened crystallized glass further contains 0 to 3.00 wt % BaO and / or 0 to 2.00 wt % Y. 2 O 3 and / or The chemically strengthened crystallized glass contains TiO 2 and P 2 O 5 Basically, it does not include The glass-ceramics for chemical strengthening according to claim 15 or 16,
18. A glass instrument manufactured from the strengthened crystallized glass according to any one of claims 1 to 14, or manufactured from the chemically strengthened crystallized glass according to any one of claims 15 to 17.
19. An electronic device comprising the strengthened crystallized glass according to any one of claims 1 to 14 or the chemically strengthened crystallized glass according to any one of claims 15 to 17.
Citation Information
Patent Citations
Microcrystalline glass, microcrystalline glass product and manufacturing method thereof
CN111807705A
Tempered glass, microcrystalline glass and preparation method and application thereof
CN115286251A
Crystallized glass substrate
WO2020031339A1